Introduction to video production school of video miscellaneous (Australia : Southern Television Copporation PTY LTD, 1992)
The school of video has been established to give you the unique opportunity to learn about video production from the people involved in professional television production
Copy available in DVD format
Keywords: Television -- Production and direction